PENGOLAHAN AIR LINDI DENGAN PROSES KOMBINASI BIOFILTER ANAEROB-AEROB DAN WETLAND - Hadiwidodo, Mochtar; Oktiawan, Wiharyanto (Universitas Diponegoro, 2012)
In Indonesia leachate is still an issue yet to be addressed. With a high content of pollutant parameters and lack of government support resulting landfill must think about the appropriate treatment to be safe for treating waste when discarded into the environment. Biofilter methods and wetland is the one of alternatives leachate treatment that can be used. This method does not require a large operating costs and does not require skilled professionals to operate it. With a combination of wetland and biofilter, it is expected to reduce the content of pollutants inÂ the leachate, so it can be meet the wastewater quality standards which set by the government. The levels of pollutants were tested in this study is the BOD5, COD, TSS, ammonia, nitrite and nitrate.